The beta c component of the granulocyte-macrophage colony-stimulating factor (GM-CSF)/interleukin 3 (IL-3)/IL-5 receptor interacts with a hybrid GM-CSF/erythropoietin receptor to influence proliferation and beta-globin mRNA expression. - Jubinsky, P. T. (The Feinstein Institute for Medical Research, 1996)
BACKGROUND: The interaction of different members of the hematopoietic growth factor receptor family may be relevant to the increased proliferation and the failure of differentiation that characterizes the myeloid leukemias. We recently demonstrated that a chimeric receptor (GMER) that is composed of the extracellular and transmembrane domains of the human granulocyte-macrophage colony-stimulating factor (GM-CSF) receptor alpha-chain (GMR alpha) and the cytoplasmic domain of the murine erythropoietin receptor mEpoR binds hGM-CSF with low affinity (3 nM) and confers both proliferative and differentiation signals to stably transfected murine Ba/F3 cells. MATERIALS AND METHODS: To investigate whether the common beta-subunit of the GM-CSF receptor (beta c) can interact with GMER, either the entire beta-subunit or a mutant, truncated beta-subunit that completely lacks the cytoplasmic domain (beta tr) was introduced into Ba/F3 cells that express GMER, and the binding of GM-CSF as well as proliferation and differentiation responses were measured. RESULTS: Scatchard analysis showed that both GMER + beta c and GMER + beta tr bound hGM-CSF with high affinity (Kd 40 pM to 65 pM). Proliferation assays showed that the maximum growth of cells expressing GMER + beta c was identical to that of cells with GMER alone. However, proliferation of the cells that expressed GMER + beta tr was reduced by 80-95% of GMER. Dose-response curves showed that the concentration of GM-CSF required for half-maximal growth was 0.5-5.0 pM for GMER + beta c and 0.5-5 nM for GMER and GMER + beta tr. The EpoR cytoplasmic domain of GMER also undergoes ligandinducible tyrosine phosphorylation. However, the tyrosine phosphorylation did not correlate with growth in cells expressing beta tr. Coexpression of beta c with GMER in Ba/F3 cells grown in hGM-CSF markedly enhanced beta-globin mRNA expression. CONCLUSIONS: These results indicate that beta c can transduce a unique signal in association with GMER to influence both proliferative and differentiation signal pathways.